2008
DOI: 10.1016/j.yjmcc.2008.02.274
|View full text |Cite
|
Sign up to set email alerts
|

Allele and species dependent contractile defects by restrictive and hypertrophic cardiomyopathy-linked troponin I mutants

Abstract: Restrictive cardiomyopathy (RCM) is a debilitating disease characterized by impaired ventricular filling, reduced ventricular volumes, and severe diastolic dysfunction. Hypertrophic cardiomyopathy (HCM) is characterized by ventricular hypertrophy and heightened risk of premature sudden cardiac death. These cardiomyopathies can result from mutations in the same gene that encodes for cardiac troponin I (cTnI). Acute genetic engineering of adult rat cardiac myocytes was used to ascertain whether primary physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…The results of this study are generally consistent with those from in vitro reconstituted protein and isolated experimental animal skinned myocardium studies, including the drastic increase in Ca 2ϩ sensitivity (9). Either a decrease (9) or, as in the present study, an increase (36) in maximum force development has been reported for the RCM-associated cTnI R145W mutation; most reports on the HCM-associated cTnI R145G mutation show a decrease in this parameter (10,11,35,37). Whether this reflects a genuine difference between the HCM-associated R145G mutation and the R145W RCM-associated mutation that we examined in the present study remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study are generally consistent with those from in vitro reconstituted protein and isolated experimental animal skinned myocardium studies, including the drastic increase in Ca 2ϩ sensitivity (9). Either a decrease (9) or, as in the present study, an increase (36) in maximum force development has been reported for the RCM-associated cTnI R145W mutation; most reports on the HCM-associated cTnI R145G mutation show a decrease in this parameter (10,11,35,37). Whether this reflects a genuine difference between the HCM-associated R145G mutation and the R145W RCM-associated mutation that we examined in the present study remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the R92Q (56), R145G (57), R145W (58), ⌬160 (56), A172T (59), and R193H (9,60) mutations in cTnI all increase the myofilament Ca 2ϩ sensitivity and prolong SL relaxation times in isolated cardiomyocytes. Similarly, the older R21C mice have adapted by delaying the sarcomere relaxation time of myocytes, even in the absence of ␤-AR stimulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, HCM and RCM mutations have been shown to increase the Ca 2ϩ sensitivity of the myofilament (4,25). In vitro thin filament reconstitution experiments, with the only variable being the mutated protein, have shown that HCM and RCM mutations increase Ca 2ϩ sensitivity, with RCM mutations causing a larger increase than HCM mutations (2,4,34).…”
mentioning
confidence: 99%
“…In vitro thin filament reconstitution experiments, with the only variable being the mutated protein, have shown that HCM and RCM mutations increase Ca 2ϩ sensitivity, with RCM mutations causing a larger increase than HCM mutations (2,4,34). From a molecular standpoint, these two diseases are a continuum of the same disease mechanism.…”
mentioning
confidence: 99%
See 1 more Smart Citation